A look at the statte of the art of wine tourism - Franco Mendívil, Gerardo (Posgrados de la División de Ciencias Económica Administrativas, 2021)
This work is the result of a broader research project. However, when developing the stages of this, the researchers came across a lack of information regarding the state of wine tourism and from what points of view it has been studied and what the results have been. Hence, a search for bibliographic information begins in all the printed and electronic media that were available to date, to concentrate it and facilitate the study, analysis or consultation of the subject that is currently being addressed: Wine tourism. The document is divided into several sections. The first allows us to know the countries and regions that currently implement wine tourism activity, as a complementary action to viticulture and in a second section, it deals with the importance and economic weight of it on an international, Latin American and national scale. Up to the first stage of the investigation, the information findings, antecedents, type cases, that allow to obtain a first look at the object of study: Wine tourism.